Laymen's Narratives in Amouddou's Eco-documentary: An Ecolinguistic Analysis - Mohamed Mliless; Lamiae Azzouzi; Saida Hdii; Handoko Handoko (JURNAL ARBITRER, 2021)
Documentary films, generally of short or medium-length, have informative and educational purposes. They present authentic reports on areas of life, human activities, and the natural world. Particularly, eco-documentaries aim to raise environmental awareness towards the degradation of natural elements; they present alternatives for environmental issues such as pollution, global warming, and deforestation. To reinforce the argumentative process of environmental documentaries, laymen discourse contributes a lot to the meaning-making of productions. Within the framework of discourse analysis and ecolinguistics, this work examines fear and threat expressions used by ordinary witnesses to reinforce argumentation in Lahoucine Faouzi's eco-documentary entitled "Whining of the Blue Lagoon". In this vein, the 'perceived severity and perceived susceptibility' model was used to investigate the implication of fear and threat appeals in laymen's testimonies. The results show that these expressions are common among laymen's narratives. This study has many implications for eco-documentary makers, governmental and non-governmental organs, and future research to explore other linguistic features in eco-documentaries on man's perpetrated damages to the environmental resources.